Agarwood (Aquilaria malaccencis) Health at Nursery - Dina Naemah; Hat Mayani Diah Ningrum (Journal of Wetlands Environmental Management, 2015)
Gaharu (Aquilaria malaccencis) is a tree species included in Thymelleaceae family, Agarwood can grow inlowland as well as mountains, up to 750 m above sea level. The average temperature required is 32 Â° C andthe average humidity is 70%, with annual rainfall of about 2000 mm. This plant produces a resin powderwhich has a distinctive aroma fragrance infected due to fungal diseases (fungi) that enter through the trunkwound. The objective of this study is to identify the characteristics of attack which causes damage to theagarwood plant seedlings (Aquilaria malaccencis) and to elucidate the intensity of pests and diseases onagarwood plant seedling (Aquilaria malaccencis). By using code of Environmental Monitoring andAssessment Program (EMAP) which had been modified so that it was obtained the damage cause, damagedparts of plants, the type and the level of severity of damage suffered by the plant. Based on the results, datashowed that the biggest cause of the damage suffered by the agarwood plant was a disease characterized bysymptoms on the leaves where the damage type was in the form of leaf discoloration with the level ofseverity of 20-29%. The intensity of damage was 44. 66%, damage due to pest was 8%, and damage due toillness was 32%.